TOWARD KNOWLEDGE SOCIETIES IN THE GANDHIAN PERSPECTIVE AND THE CIVIL RIGHTS MOVEMENT - Lyons, Ivory (Journal of Dharma, 2019)
Mohandas K Gandhi and Martin Luther King, Jr as disciples of nonviolence fought against oppression. Gandhi and King strove to learn beyond what their schools taught them and became better educated men. Gandhi had a vision and King a dream. Through education Gandhi helped those who had King’s dream to connect the dream with the vision to deal with the awful reality of injustice and helped to make the world a better place. This paper through the four Pillars of Learning will demonstrate how Gandhi impacted the Civil Rights Movement with his vision and how leaders of the Civil Rights Movement and King among them appropriated the vision of Gandhi and used nonviolence as a tool to deal with the oppression under which they lived.